Phenomenology of Non-Suicidal Self-Injury among Female High School Students in Ardabil City in the Academic Year 2018-2019 - Zahra Mohebbi; Hossein Ghamari-Givi; Mohammad Reza Falsafinejad; Anahita Khodabakhshi-koolaee (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objective: Non-suicidal self-injury has become public health challenge in recent years. The prevalence of this phenomenon is higher among adolescents than other age groups. However, there are many ambiguities in conceptualizing non-suicidal self-injury. The objective of this study was to investigate the experiences of female high school students in Ardabil city who had committed non-suicidal self-injury. Materials and Methods: This qualitative descriptive phenomenology study was conducted with participation of 17 female high school students in Ardabil city who were selected via targeted sampling method in 2018-2019. Data were collected via semi-structured interview sessions. Colaizzi's seven-step analysis method was used for data analysis. Results: The findings of the study showed three main categories include predisposing factors of self-injury, function of self-injury, and consequences of self-injury. The main categories were subcategorized into cognitive emotional features, incompatible relations, teenage problems in the family, calming down, forgetting the problems, impressing others, proving greatness and strength, feelings of regret and scarring. Conclusion: To better understand people involved with non-suicidal self- injury, it is essential to become more familiar with their experiences. From the participants̓ point of view, this behavior has underlying causes, functions, purposes and also the implications that should be addressed for prevention programs as well as proper evaluation and treatment. Ethical code: IR.IAU.SRB.REC.1397.099 DOI: http://doi.org/10.22037/ch.v7i3.25327